Population of Phosphate Solubilizing Bacteria in Maize Rhizosfer with Different Irrigation Volume and Organic Matter - Shakila, Nur Asri; Susilowati, Lolita Endang; Dewi, Rika Andriati Sukma; Suriadi, Ahmad (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Phosphate solubilizing bacteria are soil bacteria which is vital to converting non-available phosphate into available phosphate. There has been a lot of studies to find out strategies or treatments that can increase PSB populations and activities, such as addition of organic materials or irrigation technique. This research aimed to test the effect of different irrigation volumes and types of organic material on phosphate solubilizing bacteria in maize rhizosphere. This research is a field experiment with a split plot design with two factors, irrigation volume (I1: 100% of plant needs, I2: 80% of plant needs, and I3: 60% of plant needs) as the main plot and type of organic material ( B0: without organic material, B1: manure; B2: rice husk biochar, and B3: vermicompost + biochar) as the sub plots. Soil and crop samples were taken at maximum vegetative phase (56 days after planting). The parameters tested and observed in this research were PSB population, soil pH, soil organic carbon, available P, phosphate uptake, and soil moisture. Based on the results of this research, it was obtained that the interaction between the irrigation volume of 100% of plants needs and the manure gave the highest PSB population about 1,23 x 106 cfu/gram. This population increase is in line with an increase in soil-available P and plant phosphate uptake.